African American patient knowledge of kidney disease: A qualitative study of those with advanced chronic kidney disease. (December 2015) - Kazley, Abby S; Johnson, Emily; Simpson, Kit; Chavin, Kenneth; Baliga, Prabhakar
Kidney disease is a costly and prevalent condition that affects African Americans more than any other group. The purpose of this study was to determine the knowledge of kidney disease African American patients have about their disease. Four qualitative focus groups were conducted with kidney disease patients in which the patients gave thoughts and opinions on kidney disease and various components and factors of the condition. The data were independently reviewed and analyzed using Qualrus coding software. Dominant themes discussed in the focus groups included: causes of kidney disease, patient thoughts on dialysis as a treatment for kidney disease, information source for disease knowledge, thoughts on God and faith, reaction to kidney disease, and types of treatment available. The study found that the majority of patients were unaware of specific causes and risk factors of kidney disease, were unsure of available treatments, and had a severe lack of knowledge and support system in dealing with the condition. Early prevention and education programs aimed at high-risk populations would be very beneficial in decreasing the incidence and increase of kidney disease.